2016
DOI: 10.1177/0265407515611494
|View full text |Cite
|
Sign up to set email alerts
|

“She chose us to be your parents”

Abstract: Guided by narrative theorizing, the current study investigated the content and process of telling adoption entrance narratives (AENs)-or the story of how the child was born, placed for adoption, and integrated into their family-in open adoptive families. Thematic analysis of 165 adoptive parents' (mostly mothers) AENs revealed six emergent themes: birth parents as family, chosen parents, forever, rescue, fate, and adoption makes us family. Structural equation modeling demonstrated that adoptive mothers' relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 32 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Hays et al discovered, through the entrance narrative, that parents socialized their child to view and understand adoption in positive ways. In so doing, the content and process of telling the entrance narrative upheld one another and positively affected relationships among individuals in the adoption kinship network (Hays et al, 2015). Similarly, results from a study conducted by Kranstuber and Kellas (2011) on closed adoption entrance narratives revealed the significance of the themes of chosen child, negative reconnection, and difference on adult adoptee's self-concept.…”
Section: Phase 1: the Adoption Or Foster Storymentioning
confidence: 92%
See 4 more Smart Citations
“…Hays et al discovered, through the entrance narrative, that parents socialized their child to view and understand adoption in positive ways. In so doing, the content and process of telling the entrance narrative upheld one another and positively affected relationships among individuals in the adoption kinship network (Hays et al, 2015). Similarly, results from a study conducted by Kranstuber and Kellas (2011) on closed adoption entrance narratives revealed the significance of the themes of chosen child, negative reconnection, and difference on adult adoptee's self-concept.…”
Section: Phase 1: the Adoption Or Foster Storymentioning
confidence: 92%
“…Adoptive parents take the lead in establishing the extent to which adoptive and birth family members will interact after adoption (Neil, Beek, & Schofield, 2003). In fact, research has revealed that adoptive parents often serve as gatekeeper between the adopted child and birth parent(s) (Hays, Horstman, Colaner, & Nelson, 2015) such that adoptive parents often provide vital information and tell stories that may affect the adoptee-birth parent relationship (Colaner, Halliwell, & Guignon, 2014;Hays et al, 2015). Yet as adoptees transition to adulthood, their roles in the family may shift; adoptees may begin making independent decisions about contact and initiating conversations about adoption (Farr, Grant-Marsney, & Grotevant, 2014).…”
Section: Communicatively Negotiating Birthmentioning
confidence: 99%
See 3 more Smart Citations